2005
DOI: 10.1080/02841860500327586
|View full text |Cite
|
Sign up to set email alerts
|

Serum tartrate-resistant acid phosphatase 5b (TRACP 5b) as a marker of skeletal changes in prostate cancer

Abstract: Skeletal metastases are a significant problem in prostate cancer (PC). The patients are also exposed to treatment-related skeletal changes. This cross-sectional study evaluated a marker of bone resorption, TRACP 5b in relation to the standard analyte total alkaline phosphatase (tALP) as a marker of skeletal changes. Serum levels of TRACP 5b, tALP and PSA were measured in 130 prostate cancer patients. Comparison was made between patients with (BM+, n = 25) and without (BM-, n = 105) skeletal metastases, and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Both serum alkaline phosphatase and serum tartrate-resistant acid phosphatase were reported to be able to predict BM from PCa [18,19]. A combination of tartrate-resistant acid phosphatase, alkaline phosphatase and PSA can obviate the need for a bone scan in 70% of cases [20].…”
Section: Discussionmentioning
confidence: 99%
“…Both serum alkaline phosphatase and serum tartrate-resistant acid phosphatase were reported to be able to predict BM from PCa [18,19]. A combination of tartrate-resistant acid phosphatase, alkaline phosphatase and PSA can obviate the need for a bone scan in 70% of cases [20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TRAP has been studied extensively as a serum marker of bone resorption in cancer patients [16][17][18][19]. The serum activity of TRAP can be used to monitor treatment efficiency and recurrence of bone metastasis in breast [20] and prostate [21] cancer patients. These studies indicate that TRAP can be utilized as a marker for progression of metastatic bone disease and suggest that the enzyme could also be a potential target for future cancer therapies.…”
mentioning
confidence: 99%
“…In this study, the TRACP 5b cutoff was 5.0 U/L, according to a study conducted by Salminen et al [17], who analyzed TRACP 5b as a marker of skeletal changes in patients with prostate cancer using the Bone TRAP Assay.…”
Section: Resultsmentioning
confidence: 99%
“…For TRACP 5b concentrations obtained in our study, we identified the optimal cutoff value at 50.0 U/L in ROC analyses. After applying the cutoff of 50.0 U/L instead of the cutoff 5.0 U/L recommended by Salminen et al [17], the quality parameters of the TRACP 5b analysis changed. Sensitivity decreased to 47.1% from 76.5%; however, the specificity increased considerably to 96.7% from 36.7%.…”
Section: Bone Trap Assaymentioning
confidence: 99%